Development of a Curriculum to Enhance Growth Mindset for Junior High School Students - Mungueamklang, Jaruwan; Naowanondha, Adisorn; Sutthirat, Chaiwat (Ratchaphruek Journal, 2023)
This research aims: 1) to study the mindset growth of junior high school students. 2) Develop a curriculum to enhance the growth mindset. 3) to study the effect of using the curriculum. And 4) to assess and improve the curriculum. Five junior high school students who have the participated in the activity with an attached mindset. This research was conducted in 4 steps: 1) study the mindset growth of students by using the mindset growth test. 2) Development curriculum. 3) Curriculum outcome studies and 4) Evaluation and Improvement the curriculum. The method used to collect data was: Conceptual measurement form, observation form, data analysis using percentage, mean, standard deviation statistics and Wilcoxon Signed Ranks Test. The findings of research were as follows: 1) Secondary school students had mixed concepts. 2) The Curriculum is appropriate to a large extent.3) Students who participating with the post- growth mindset curriculum has higher than the pre-growth mindset curriculum, achievement at a significant level of .05. and 4) The curriculum could be appropriate, consistent and could be able to enhance growth mindset. And the student’s satisfaction towards the learning curriculum was very satisfied at the high level.